Aerobic fitness and performance in elite female futsal players - Barbero-Alvarez, J. C.; Subiela, J. V.; Granda-Vera, C.; Castagna, M.G.; Del Coso, J. (Biology of Sport, 2015)
Despite its growing popularity, few studies have investigated specific physiological demands for elite female futsal. The aim of this study was to determine aerobic fitness in elite female futsal players using laboratory and field testing. Fourteen female futsal players from the Venezuelan National team (age =21.2±4.0 years; body mass =58.6±5.6 kg; height =161±5.0 cm) performed a progressive maximal treadmill test under laboratory conditions. Players also performed a progressive intermittent futsal-specific field test for endurance, the Futsal Intermittent Endurance Test (FIET), until volitional fatigue. Outcome variables were exercise heart rate (HR), VO2, post-exercise blood lactate concentrations ([La]b) and runn ing speeds (km · h-1). During the treadmill test, VO2max, maximal aerobic speed (MAS), HR and peak [La]b were 45.3±5.6 ml · kg-1 · min-1, 12.5±1.77 km · h-1, 197±8 beats · min-1 and 11.3±1.4 mmol · l-1, respectively. The FIET total distance, peak running velocity, peak HR and [La]b were 1125.0±121.0 m, 15.2±0.5 km · h-1, 199±8 beats · min-1 and 12.5±2.2 mmol · l-1, respectively. The FIET distance and peak speed were strongly associated (r= 0.85-87, p<0.0001) with VO2max and MAS, respectively. Peak HR and [La]b were not significantly different between tests. Elite female futsal players possess moderate aerobic fitness. Furthermore, the FIET can be considered as a valid field test to determine aerobic fitness in elite level female futsal players.